2015
DOI: 10.2807/1560-7917.es2015.20.27.21182
|View full text |Cite
|
Sign up to set email alerts
|

National point prevalence survey of healthcare-associated infections and antimicrobial use in French home care settings, May to June 2012

Abstract: In May and June 2012, a national point prevalence survey (PPS) of healthcare-associated infections (HAIs) and antimicrobial use was conducted among French patients under home-based hospital care (HBHC). Data from 5,954 patients in 179 volunteer HBHC providers were collected. Prevalence of patients with at least one active HAI was 6.8% (95% confidence interval (CI): 6.1-7.4). Prevalence of those receiving at least one antimicrobial agent was 15.2% (95% CI: 14.3-16.1). More than a third (35.5%) of HAIs were HBHC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…This may be due to patients recruited from different home-based populations, e.g. dedicated home healthcare agencies or hospital home-based care and therefore comparisons are not applicable (Miliani et al, 2015; RCP, 2012; Sorbye et al, 2005). The mean age of people in our study and the prevalence of suprapubic catheters were higher than that reported in similar sample populations by Wilde et al (2010, 2013), with a larger number of men than reported by Getliffe and Newton (2006) and Wilde et al (2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may be due to patients recruited from different home-based populations, e.g. dedicated home healthcare agencies or hospital home-based care and therefore comparisons are not applicable (Miliani et al, 2015; RCP, 2012; Sorbye et al, 2005). The mean age of people in our study and the prevalence of suprapubic catheters were higher than that reported in similar sample populations by Wilde et al (2010, 2013), with a larger number of men than reported by Getliffe and Newton (2006) and Wilde et al (2013).…”
Section: Discussionmentioning
confidence: 99%
“…Catheter-associated urinary tract infections (CAUTI) are associated with increased patient morbidity and mortality resulting in increased healthcare use and cost (Lo et al, 2014). Prevalence studies report that 12–21% of patients in acute hospitals and 6–13% in the community have an IUC, making it the most common indwelling device in use (Health Protection Surveillance Centre [HPSC], 2012, 2013; Miliani et al, 2015; Royal College of Physicians [RCP], 2012).…”
Section: Introductionmentioning
confidence: 99%
“…ESH' den yararlanan hastalarda İYE sık görülmektir [13]. Yurt dışında ve yurt içinde yapılan çeşitli çalışmalarda ESH' den yararlanan hastalarda İYE görülme oranı %23-26 olarak bulunmuştur [6,14]. Yurt dışında ESH yapılan çalışmada, İYE en fazla neden olan pato- [9].…”
Section: Sondayla İlişkili İdrar Yolu Enfeksiyonları: Farklı Hasta Pounclassified
“…2018.33087 Saúde (OMS), com base em relatórios elaborados pelo Institute of Medicine dos Estados Unidos, apontam que 1,4 milhões de pessoas adquirem infecções anualmente. Na Europa, aproximadamente 6,8% dos pacientes internados adquirem, pelo menos, uma IRAS, e este número se torna ainda mais agravante em países em desenvolvimento, onde o risco de contrair infecções é quatro vezes maior 2,3 .…”
Section: Introductionunclassified